A study on technostress among first semester postgraduate students in Universiti Teknologi Mara, Shah Alam / Siti Nur Farrah Faadiah Ab Ghani... [et al.] - Ab Ghani, Siti Nur Farrah Faadiah; Ismail, Siti Nasarah; Manshor, Maizura; Sah Allam, Siti Nurshahidah; Ramlan, Aini Faezah; Abdul Latiff, Dzaa Imma (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Technology stress (Technostress) can be defined as a modern disease of adaptation caused by an inability to cope with new computer technologies in a healthy manner. Clear symptoms of Technostress include inability to concentrate on a single issue, increased irritability and feeling of loss of control. The study was conducted among 1st semester postgraduate students in Universiti Teknologi MARA, Shah Alam in order to measure the level of their stress. Domains of Technostress can be classified as learning, border, communication, time, family, workplace, and societal perception of technology. The instrument, Personnel Technostress Inventory (PTSI) created by Rosen & Weil (1999), was revised, simplified and finalized according to the research objectives. Result shows that family technostress is the major domain experienced by participants apart from having a moderate level of technostress.